Improving Writing a Descriptive Paragraph of Elementary School Students through Picture-Based Mind Mapping - Tarman A Arief; Arwan Wiratman (Jurnal Ilmiah Sekolah Dasar, 2023)
The skill of writing descriptive paragraphs is one of the lessons that are difficult for elementary school students to understand. This study aims to analyze the effect of media image-based mind mapping on the skills of writing descriptive paragraphs of elementary school students. This study used quantitative research with a quasi-experimental design method with a Non-equivalent control group type. In this study, two groups were not randomly selected. Both groups were given a pretest to determine the initial state. The experimental group was treated with image media-based mind mapping, while the control group was image-based. Data collection techniques using observation and test sheets writing descriptive paragraphs. Assessment of the quality of writing descriptive paragraphs is based on focus, development, unity, coherence, and correctness. The collected data will be analyzed through two analyzes, namely descriptive statistical analysis and inferential statistical analysis. The results of the study show that image media-based mind mapping has a significant effect on improving the skills of writing descriptive paragraphs in elementary school students. Image media-based mind mapping inspires students to write because it can develop and describe the ideas they want to write in a clearer and well-structured manner.